2021
DOI: 10.1093/mnras/stab583
|View full text |Cite
|
Sign up to set email alerts
|

Detection of spectral variations of Anomalous Microwave Emission with QUIJOTE and C-BASS

Abstract: Anomalous Microwave Emission (AME) is a significant component of Galactic diffuse emission in the frequency range 10-60 GHz and a new window into the properties of sub-nanometre-sized grains in the interstellar medium. We investigate the morphology of AME in the ≈10○ diameter λ Orionis ring by combining intensity data from the QUIJOTE experiment at 11, 13, 17 and 19 GHz, and the C-Band All Sky Survey (C-BASS) at 4.76 GHz, together with 19 ancillary datasets between 1.42 and 3000 GHz. Maps of physical parameter… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 99 publications
0
25
3
Order By: Relevance
“…The fidelity of our study is likely most limited by the reliability of the AME maps, which result from an extensive and challenging component separation analysis (Planck Collaboration X 2016). While additional multifrequency data have in general validated the Planck Collaboration X (2016) AME maps, systematic discrepancies have been noted at the ∼10-20% level (Dickinson et al 2019;Poidevin et al 2019;Cepeda-Arroita et al 2021). In particular, the AME is often underestimated and free-free emission overestimated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fidelity of our study is likely most limited by the reliability of the AME maps, which result from an extensive and challenging component separation analysis (Planck Collaboration X 2016). While additional multifrequency data have in general validated the Planck Collaboration X (2016) AME maps, systematic discrepancies have been noted at the ∼10-20% level (Dickinson et al 2019;Poidevin et al 2019;Cepeda-Arroita et al 2021). In particular, the AME is often underestimated and free-free emission overestimated.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, a recent study of the ρ Oph molecular cloud on arcminute scales found that PAH emission is much better correlated with AME than is the FIR dust emission (Arce-Tord et al 2020). Degree scale studies of AME in λ Orionis have found comparable levels of correlation between AME and either FIR emission or PAH emission (Bell et al 2019;Cepeda-Arroita et al 2021). However, Bell et al (2019) found a significantly stronger correlation between PAH mass and AME than between total dust mass and AME in λ Orionis.…”
Section: Introductionmentioning
confidence: 95%
“…In this work we will use a preliminary version of the C-BASS data, similar to that used by Dickinson et al (2019) and Cepeda-Arroita et al (2021). In the following sections we give an overview of the C-BASS data reduction pipeline.…”
Section: C-bass Northmentioning
confidence: 99%
“…In previous C-BASS papers (Irfan et al 2015; 1 Defined in brightness temperature units as T b ∝ ν β . Dickinson et al 2019;Cepeda-Arroita et al 2021) this resulted in an effective calibration uncertainty due to the beam of approximately 5 per cent.…”
Section: Deconvolutionmentioning
confidence: 99%
See 1 more Smart Citation